Glymphatic System in the Central Nervous System, a Novel Therapeutic Direction Against Brain Edema After Stroke - Zhou, Xiangyue; Li, Youwei; Lenahan, Cameron; Ou, Yibo; Wang, Minghuan; He, Yue (Frontiers in Aging Neuroscience, 2021)
Stroke is the destruction of brain function and structure, and is caused by either cerebrovascular obstruction or rupture. It is a disease associated with high mortality and disability worldwide. Brain edema after stroke is an important factor affecting neurologic function recovery. The glymphatic system is a recently discovered cerebrospinal fluid (CSF) transport system. Through the perivascular space and aquaporin 4 (AQP4) on astrocytes, it promotes the exchange of CSF and interstitial fluid (ISF), clears brain metabolic waste, and maintains the stability of the internal environment within the brain. Excessive accumulation of fluid in the brain tissue causes cerebral edema, but the glymphatic system plays an important role in the process of both intake and removal of fluid within the brain. The changes in the glymphatic system after stroke may be an important contributor to brain edema. Understanding and targeting the molecular mechanisms and the role of the glymphatic system in the formation and regression of brain edema after stroke could promote the exclusion of fluids in the brain tissue and promote the recovery of neurological function in stroke patients. In this review, we will discuss the physiology of the glymphatic system, as well as the related mechanisms and therapeutic targets involved in the formation of brain edema after stroke, which could provide a new direction for research against brain edema after stroke.